2003
DOI: 10.1152/ajpcell.00501.2002
|View full text |Cite
|
Sign up to set email alerts
|

K+ depolarization induces RhoA kinase translocation to caveolae and Ca2+ sensitization of arterial muscle

Abstract: KCl causes smooth muscle contraction by elevating intracellular free Ca2+, whereas receptor stimulation activates an additional mechanism, termed Ca2+ sensitization, that can involve activation of RhoA-associated kinase (ROK) and PKC. However, recent studies support the hypothesis that KCl may also increase Ca2+ sensitivity. Our data showed that the PKC inhibitor GF-109203X did not, whereas the ROK inhibitor Y-27632 did, inhibit KCl-induced tonic (5 min) force and myosin light chain (MLC) phosphorylation in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
91
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 49 publications
17
91
0
Order By: Relevance
“…In the present study, the Rho-kinase inhibitor Y-27632 dose dependently reduced the contraction but not the increase in [Ca 2ϩ ] i induced by KCl, which suggests that Rho kinase is involved in Ca 2ϩ sensitization evoked by depolarization and confirms previous reports in arterial smooth muscle from several vascular beds (15,24,32). The inhibitory effect of Y-27632 on the contractions of both [Ca 2ϩ ]-clamped ␣-toxin-permeabilized arteries and on those induced by K ϩ depolarization in intact arteries suggests that both Ca 2ϩ -independent and -dependent mechanisms, respectively, are involved in the Rho kinase-mediated Ca 2ϩ sensitization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, the Rho-kinase inhibitor Y-27632 dose dependently reduced the contraction but not the increase in [Ca 2ϩ ] i induced by KCl, which suggests that Rho kinase is involved in Ca 2ϩ sensitization evoked by depolarization and confirms previous reports in arterial smooth muscle from several vascular beds (15,24,32). The inhibitory effect of Y-27632 on the contractions of both [Ca 2ϩ ]-clamped ␣-toxin-permeabilized arteries and on those induced by K ϩ depolarization in intact arteries suggests that both Ca 2ϩ -independent and -dependent mechanisms, respectively, are involved in the Rho kinase-mediated Ca 2ϩ sensitization.…”
Section: Discussionsupporting
confidence: 92%
“…Although Rho kinase is activated by excitatory agonists via receptors coupled to the G ␣12/13 family of heterotrimeric G proteins (10), recent studies have demonstrated that Ca 2ϩ sensitization involving Rho-kinase activation can also be brought about by membrane depolarization (15,24,32). In the present study, the Rho-kinase inhibitor Y-27632 dose dependently reduced the contraction but not the increase in [Ca 2ϩ ] i induced by KCl, which suggests that Rho kinase is involved in Ca 2ϩ sensitization evoked by depolarization and confirms previous reports in arterial smooth muscle from several vascular beds (15,24,32).…”
Section: Discussionmentioning
confidence: 99%
“…RhoA and Rho kinase exhibit activity-dependent translocation to caveolae (62,65), suggesting a role for cholesterol depletion-induced changes in caveolae organization. Interestingly, caveolae are also sensitive to cell volume perturbations (46), and have been implicated in VRAC regulation (63,64).…”
Section: Discussionmentioning
confidence: 99%
“…In vascular endothelial cells (7,42) and NIH3T3 cells (47) the activity of the Rho-associated kinase (Rho kinase; ROK) is required for VRAC activation. RhoA and ROK associate with rafts and caveola and translocate to caveolae in an activationdependent manner (62,65), raising the possibility that the effect of cholesterol depletion on VRAC might involve changes in Rho kinase activity.…”
mentioning
confidence: 99%
“…KClevoked contraction has been linked to the activation of Rho kinase (Urban et al, 2003). Moreover, Rho kinase has also been implicated in events leading to Ca 2+ entry in vascular muscle distinct from voltage-or store-operated channels in rat aorta and mesenteric arteries (Ghisdal et al, 2003).…”
Section: Other Signaling Pathwaysmentioning
confidence: 99%